Wage System Manufacturing Company: Normative and Expectations - ., Arniati; Gunawan, Hendra; Kartikaningdyah, Ely (International Journal of Economics and Financial Issues, 2015)
The study determine the wages models applied by the company in Batam which is expected to provide a wide range of reference models in different strata of wage and cluster companies. It is also expected to help the local government as a factor in determining the minimum wage policy making through recommendations wages models are ideal in Batam. Data was collected using interview techniques to the manufacturing industry in three related units in a company that is human resource, administrative staff and production staff. The results of the study were analyzed qualitatively to explore models that have been applied and the desire of employees. The model has been applied to remuneration in accordance with the general models that already exist, but there are still some wishes of the employees on the compensation of employees in the company they both administrative and production employees. Researchers also analyzed employee satisfaction with the existing system and the results are most of the employees did not feel satisfied with the remuneration system. Keywords: System; Local Government; Employee; Minimum Wage; Compensation JEL Classifications: N60